Análise computacional da ponte sobre o rio Chatopauá através do software comercial SAP2000® - CARDOSO, Daniel Laredo (2025)
This work presents a detailed computational analysis of the Chatopauá Bridge, located on the Transamazonian Highway (BR-230), using the SAP2000® software. The objective is to understand the structural performance of the model under different loading conditions and structural configurations, combining computational modeling with static load test experiments. Initially, the study highlights the relevance of structural analysis as an essential tool for ensuring the safety, stability, and functionality of special structures. The use of advanced software, such as SAP2000, enables more accurate calculations, optimizing resources, reducing errors, and increasing project reliability. The analysis follows recognized technical standards, such as NBR 9607/2023, which outlines procedures for load tests on structures. Three computational models were developed, varying the configurations of longitudinal and transverse beams, and subjected to simulated static tests. During the tests, loads were applied at different positions to monitor displacements and deformations. The results of these models were compared with experimental data obtained in the field, assessing the ability of each configuration to replicate the real behavior of the structure. The results showed that each model has specific characteristics and advantages. Model 1 stood out for its high structural rigidity, ideal for situations where minimizing deformations is crucial. Model 2 demonstrated great compatibility with the behavior observed in the actual bridge, making it suitable for projects that prioritize stability and structural fidelity. Finally, Model 3 was the most accurate in reproducing experimental tests, providing detailed data that enrich theoretical validation. It is concluded that computational analysis is indispensable in modern engineering, allowing precise and safe simulations that minimize risks and optimize projects. This study reinforces the importance of integrating computational modeling into the analysis and design process, recommending the use of tools such as SAP2000 and suggesting, for future studies, the exploration of other advanced software, such as ANSYS and CSI Bridge, to expand the possibilities for structural analysis and validation.